Knowing God intimately : being as close to Him as you want to be - Meyer, Joyce, 1943- (New York : Warner Faith, 2003)
Identifies four levels of Christian intimacy, advising how to pursue a self-motivated relationship with God and sharing biblical examples and the author's own personal experiences.
Includes bibliographical references (p. [291]-296).
Keywords: God (Christianity) -- Knowableness; Spirituality